การพัฒนากระบวนการจัดทำแฟ้มสะสมงานเพื่อประเมินผลการเรียนรู้ของผู้เรียนที่ได้รับการจัดการเรียนการสอนตามแนวการเรียนรู้เพื่อสร้างสรรค์ด้วยปัญญาแบบเต็มรูปในโรงเรียนดรุณสิกขาลัย - กมลวรรณ ตังธนกานนท์ (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
The purposes of this study were (1) to develop a process of organizing portfolios for students taught by full-scale constructionism approach by using participatory action research, and (b) to analyze the development of students academic achievements and desirable characteristics assessed by the developed portfolios. The sample were 12 students of Darunsikkhalai School. Participatory action research was employed in developing portfolio organizing process. The repeated measure analysis of variance was used to analyze the development of students learning assessed by the developed portfolio for 3 points in time. It was found that the portfolio organization process consisted of 8 steps: planning the portfolio, collecting created products, selecting satisfactory products, evaluating the products, revising the products, integrating knowledge acquired from making the products, evaluating the portfolio, and presenting the portfolio to parents. Evaluation of student portfolios at three different points in time indicated significant improvement (p<.01) in both academic achievement and desirable characteristics. It was also found that the academic gain was significantly higher than desirable characteristics gain (p<.01).